Traffic engineering with MPLS in the Internet. - Xipeng Xiao (IEEE Network : the magazine of global information exchange)
This article discusses traffic engineering with multiprotocol label switching (MPLS) in an Internet service provider's network. We first review MPLS, constraint-based routing, and enhanced link state interior gateway protocols to provide a background for traffic engineering. We then discuss the general issues of designing an MPLS system for traffic engineering. The design of GlobalCenter's MPLS system is presented. Based on our experiences, a generic procedure for deploying an MPLS system is proposed. We also discuss how to provide QoS in a network with MPLS. Putting these together, we present to readers the practical issues of traffic engineering and a working solution for traffic engineering with MPLS in the Internet